Poverty in the Czech Republic: Unemployment, pensions, and regional differences - Daniel Kolář (Charles University in Prague, Institute of Economic Studies (IES), 2024)
The Czech Republic has experienced a remarkable decline in the unemployment rate but not in relative poverty. I address this and other facts by analysing the evolution of absolute and relative poverty over the 2004-2021 period. I first document a remarkable decline in absolute poverty in poorer Czech regions, indicating that the growth experience of the Czech Republic was shared. Nonetheless, the low absolute poverty levels of Western Europe are yet to be reached. I then explain the paradox of stagnating relative poverty, i.e., the at-risk-ofpoverty rate, and find that the drop in unemployment was offset by increased oldage poverty. Oaxaca-Blinder decomposition reveals that older retirees living alone are particularly vulnerable. However, the overwhelming majority of the retired poor live in their own housing, and treating imputed rent as part of income would decrease retirees' poverty.
Keywords: C38; D31; I32; 330; poverty; welfare; decomposition